Pengujian Black Box Pada Pada Sistem Informasi Hewan Qurban Berbasis Website Menggunakan Metode Teknik Equivalence Partitions - Arbi Haryanto; Muhammad Akbar Naunsaadjie; Muhamad Latief; Irfan Maulana (CV. Multi Kreasi Media, 2023)
Testing on an application aims to check whether a program has been running properly or there are still errors that must be corrected so that the program created will become a program that has good quality. In this study, the software that will be studied using Blackbox Testing is a letter archiving system consisting of 10 forms that will be filled with data for incoming letters, outgoing letters, invitations, ticket data and official notes. The type of testing of the Blackbox method varies, one of which is the Equivalence Partitions used by the author in this study. The Equivalence Partitions technique is a test based on entering data on each form in the best sales selection system, each input menu will be tested and grouped based on its function whether it is valid or invalid.